Improvement of Motor Skills and Motivation to Learn Physical Education Through the Use of Traditional Games - Aliriad, Hilmy; Adi S; Manullang, Jujur Gunawan; Endrawan, I Bagus; Satria, M. Haris (Physical Education Theory and Methodology, 2024)
Study purpose. This study aims to investigate motor skills and motivation to learn physical education through traditional games. Materials and methods. The study was conducted using an experimental method and involved 60 students from primary schools in Purwodadi District, Grobogan Regency, Indonesia. Data were collected by measuring motor skills and learning motivation through affective, cognitive and psychomotor tests that were examined for validity and reliability. In addition, students’ character was also measured through observational tests of students’ basic movement skills. The measurement of basic movement skills was carried out before and after the intervention, which lasted for 8 sessions over one month. Data analysis was carried out using the ANOVA technique, reinforced by regression of research results using SPSS 22 software. Results. The results showed that the traditional game approach had a significant effect on increasing students’ motivation to learn physical education. The traditional games approach also contributed positively to students’ learning outcomes. Through hands-on experience in these traditional games, students can develop motor skills, coordination, speed, strength, as well as cognitive aspects such as strategy, spatial intelligence and situation analysis. Conclusions. By participating in traditional games, students can understand and respect cultural heritage and broaden their horizons about cultural diversity. Suggestions for future investigations include extending the research and development activities by including a larger sample, which may provide greater statistical power to support research findings in the area of traditional games.